THE APATHY HEADED FOR JAPANESE PROPAGANDA IN IDRUS’ HEIHO : A COMPARATIVE STUDY - Harendika, Melania S.; Hapsari, Dyah Eko; Nufiarni, Rizki (Universitas Negeri Semarang, 2017)
Idrus was a noteworthy writer in Indonesian in the course of Japanese authority. His fight in being rebellious counter to the regime at that period was noticeable through his writings, which made him familiar as a frank writer. His works were then translated into English. The translated works, nevertheless, do not communicate precisely the analogous implication as they were in the source language. Putting on Zepetnek’s Expressive Mechanisms in analyzing Idrus’ Heihois advantageous in this study in accepting whether the messages in the text to be translated (TT1) are well informed in the translated text (TT2). The results show that the TT2 of Idrus’ Heihois not able to send detailed apathy headed for Japanese propaganda as it was in the TT1. Cultural and period gaps are worth mentioning to be reflected in the interpretation process.